NILAI RUJUKAN HEMATOLOGI PADA ORANG DEWASA SEHAT BERDASARKAN SYSMEX XT-1800i - T Esa; S Aprianti; M Arif; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
The reference values of laboratory tests are affected by factors such as instruments and methods of tests, which are always beingdeveloped. For these reasons, each laboratory is recommended to determine their own reference values. To determine the reference valuesof complete blood count in healthy adult people, and compare them to the reference values which is taken from the references. A crosssectional study was conducted on 200 healthy adult people, aged 18-60 years, selected during blood donation. The eight haematologicalparameters were estimated using Sysmex Xt-1800i at Dr.Wahidin Sudirohusodo Hospital. The data were analyzed statistically by SPSS11.5 programs. The reference values of leukocyte, erythrocyte, haemoglobin, hematocrit, MCV, MCH, MCHC and platelet were: 4400 to10000 /µL; %:4.2–6.2 × 106/µL; &:3.8–5.5 × 106/µL; %:12.5–17.3 g/dL; &:11.8–15.4 g/dL; %:38.1–50.4 %; &:31.1–49.7 %; 80,1to 94,3 fL, 25,9–31,9 pg, 31,4–35,2 g/dL, and %:171.2–405.1 × 103/µL; &:191.8–441.5 × 103/µL, respectively. Significant differenceswere observed in the MCH and platelet values (p< 0,005). The values found in this study were similar to the reference value commonlyused in our laboratory, except for the MCH value which was lower and the platelet value which was higher..